TCH-029 Outcomes Evaluation of an International Workgroup on Robotics: A Multicentre Study. (12th March 2013) - Bufarini, C; Marinozzi, A; Masini, C; Milani, M; Salè, E Omodeo; Russa, R La; Bultrini, B; Ragni, L; Yaniv, A; Calabrese, S
Abstract : Background: The growing demand for patient and operator safety in anticancer drug compounding led to an increasing demand for automation. As 18 hospitals have now introduced APOTEC Achemo, it became necessary to set up a round table at which all users could share their knowledge and expertise. Therefore, in 2009 a workgroup on robotics (named APOTECA Community) was established. Every year its members meet to share their needs with the manufacturer and assemble new ideas. The annual system upgrade is a consequence of the meeting. 160 new requirements, merged into 4 upgrades, have been collected up to now. The requirements can be classified into the following main topics: a friendlier user interface; software integration with medical health records; higher productivity. Purpose: To assess the results in terms of productivity following the 2012 upgrade within the APOTECA Community Materials and Methods: Five oncology pharmacies were selected for this study: University Hospital of Ancona, European Institute of Oncology, Romagna Cancer Institute, S. Camillo Hospital of Rome, Cleveland Clinic. The abovementioned pharmacies were monitored before and after the upgrade, as far as the monthly productivity with APOTEC Achemo is concerned. Results: The 5 hospitals together prepared an average of 4150 preps/month before the 2012 upgrade, while 6000 preps/month was surpassed after the installation. Productivity showed an average increase of 46%, ranging from 11% to 67%. This variability is closely correlated with the best practise and has been analysed for each case. Conclusions: The creation of a round table where the APOTECAchemo users share experiences and discuss best practise is playing an essential role in the continuous improvement of this innovative technology. The progress recorded after the latest upgrade in terms of productivity (+46%) is only one example of this powerful tool. No conflict of interest.